2013
DOI: 10.1016/j.cortex.2013.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Developmental dyscalculia is related to visuo-spatial memory and inhibition impairment

Abstract: Developmental dyscalculia is thought to be a specific impairment of mathematics ability. Currently dominant cognitive neuroscience theories of developmental dyscalculia suggest that it originates from the impairment of the magnitude representation of the human brain, residing in the intraparietal sulcus, or from impaired connections between number symbols and the magnitude representation. However, behavioral research offers several alternative theories for developmental dyscalculia and neuro-imaging also sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
313
12
17

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(374 citation statements)
references
References 90 publications
(90 reference statements)
27
313
12
17
Order By: Relevance
“…As mentioned above, most of the previous research conducted on children with DD has dealt primarily with prepotent response inhibition (e.g., Censabella & Noel, 2005;Szűcs, et al 2013), albeit with discordant results. The main aim of the present study was therefore to confirm WM impairments in children with MA and/or DD profiles and to examine the different inhibitory deficits, particularly focusing on proactive interference and prepotent response inhibition.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…As mentioned above, most of the previous research conducted on children with DD has dealt primarily with prepotent response inhibition (e.g., Censabella & Noel, 2005;Szűcs, et al 2013), albeit with discordant results. The main aim of the present study was therefore to confirm WM impairments in children with MA and/or DD profiles and to examine the different inhibitory deficits, particularly focusing on proactive interference and prepotent response inhibition.…”
Section: Discussionmentioning
confidence: 93%
“…For example, Bull andScerif (2001), andNavarro et al (2011) found that performance in the number-quantity version of the Stroop task, but not in the color-word version, correlated with math achievement. Similarly, in children with DD, both Szűcs et al (2013) and Wang et al (2012) found that group differences were only significant for numerical Stroop tasks, not for the non-numerical versions. Szűcs et al (2013) found a domain-specific effect in a task involving Arabic digit stimuli, i.e., a number-size Stroop task in which participants were asked to choose the numerically highest digit while ignoring the physical size of the digits on the screen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is closely linked with the acquisition of complex cognitive skills (Cowan, 2013) such as reading (Cain, Oakhill, & Bryant, 2004), mathematics (Dumontheil & Klingberg, 2011), and other academic subjects (Clair‐Thompson & Gathercole, 2006; Gathercole, Pickering, Knight, & Stegmann, 2003). Deficits in working memory have been identified across a range of neurodevelopmental disorders, including attention deficit hyperactivity disorder (Holmes et al., 2014; Martinussen, Hayden, Hogg‐Johnson, & Tannock, 2005), dyslexia (Smith‐Spark & Fisk, 2007), dyscalculia (Rotzer et al., 2009; Szucs, Devine, Soltesz, Nobes, & Gabriel, 2013), and language disorders (Archibald & Gathercole, 2006; Gathercole & Baddeley, 1989; Montgomery, 2000; Weismer, Evans, & Hesketh, 1999). …”
Section: Introductionmentioning
confidence: 99%
“…Además, una menor operatividad de la MT también podría interferir en la calidad de los procesos de codificación y recuperación de los hechos numéricos, procesos descritos como muy vinculados con la MT verbal (Dehaene & Cohen, 1995;Fuchs et al, 2006). En general, los resultados de este grupo de niños CDA sustentan el análisis de Szucs et al (2013), quienes proponen, después de un análisis de varias investigaciones conductuales y de imágenes cerebrales, que las dificultades que aparecen durante el aprendizaje de las matemáticas (y particularmente en la discalculia del desarrollo) se deben fundamentalmente a una disfunción en la MT visuo-espacial vinculada al funcionamiento del ejecutivo central en la MT, más que a una disfunción en el procesamiento de las magnitudes. Lo anterior lleva a considerar que, aunque las habilidades numéricas básicas también explican un porcentaje de la varianza de la eficiencia en aritmética, el origen las dificultades en el aprendizaje de las matemáticas no parece radicar solo en un déficit en el desarrollo de habilidades numéricas básicas o en el mapeo entre los símbolos numéricos y las cantidades que estos representan, como señalan las teorías actuales sobre el origen de los trastornos en el desarrollo numérico (Dehaene, 1997;Rousselle & Noël, 2007), sino que el funcionamiento de los componentes de la MT también puede estar muy involucrado en la aparición de las dificultades en el aprendizaje de las matemáticas.…”
Section: Discussionunclassified